The effectiveness of massage gun treatment combined with passive stretching in reducing non-specific lower back pain - Prasetyo, Yudik; Shafi, Sabda Husain As; Arjuna, Fatkhurahman; Rahayu, Atikah; Shahril, Mohd Izwan bin; Nor, Mohad Anizu Mohd; Otieno, Edwin Onyango (Universitas Negeri Yogyakarta, 2024)
Non-specific lower back pain is a common condition characterized by strain, muscle spasms, or weakness of the paraspinal muscles, particularly the multifidus muscle, which affects adjacent musculature such as the gluteus, hamstrings, and quadriceps. This study aimed to investigate whether massage gun treatment combined with passive stretching could reduce non-specific low back pain in patients experiencing subacute and chronic phases of this condition. This pseudo-experimental research employed a one-group pretest-posttest design with three treatments. Participants were selected using purposive sampling based on inclusion criteria: suffering from non-specific low back pain, willingness to participate, and age between 20 and 65 years. Exclusion criteria included anatomical abnormalities of the spine, fractures, open wounds, and specific spinal disorders. The visual analog scale (VAS) was used to measure pain intensity before and after each treatment session. Initial VAS scores averaged 65.6 units. Following the first treatment, scores decreased significantly to 52.1 units; subsequent reductions occurred at 42.1 units post-second treatment and 33.5 units post-third treatment. Statistical analysis revealed a significant difference across all three treatment sessions (p = 0.000 < 0.05), indicating a progressive improvement in pain control over time. Massage gun therapy coupled with passive stretching demonstrated efficacy in reducing non-specific lower back pain among participants. These findings suggest that repeated application of these interventions can lead to sustained improvements in pain management for individuals suffering from subacute and chronic non-specific low back pain conditions